Increasing Elementary School Students' Knowledge and Motivation towards Health and Fitness through Activity-Based Pocketbook - Haris, Andi Ahmad Ashar; Indahwati, Nanik; Wibowo, Sapto (Universitas Sebelas Maret, 2024)
Elementary school students' fitness is at a very poor level due to students' lack of knowledge and motivation towards health and fitness as well as a lack of teaching materials. Therefore, this research aims to increase knowledge and motivation towards health and fitness in elementary school students through the development of an activity-based pocketbook. This research used the Borg and Gall research and development method. The development of the pocketbook was carried out through several stages, namely planning, information analysis, small-scale trials, revisions, and large-scale trials, involving three experts as validators and 42 students as samples. After that, an evaluation was conducted to determine the final result of the product being developed. The results of developing an activity-based pocketbook were product feasibility and effectiveness in increasing students' knowledge and motivation towards health and fitness. Product feasibility was obtained from validator assessments covering all aspects, where the mean percentage score for material experts was 82%, media experts were 83%, and practitioners were 87%, in the very good category. Readability tests and student responses produced mean percentage scores of 85.28% and 84.45%, respectively. The effectiveness of the product was considered effective as evidenced by an increase in knowledge pretest-posttest results of 42.86 and an increase in motivation pretest-posttest results of 5.66, or a paired sample t-test with a significance value of both, as many as 0.000. Thus, the product of developing a pocketbook based on activity-based health and fitness material was feasible to disseminate in PJOK lessons, especially in phase B elementary schools, since it can increase students' knowledge and motivation